2018
DOI: 10.1021/acs.jafc.7b04307
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of P-Glycoprotein Mediated Efflux in Caco-2 Cells by Phytic Acid

Abstract: Phytic acid (IP6) is a natural phosphorylated inositol, which is abundantly present in most cereal grains and seeds. This study investigated the effects of IP6 regulation on P-glycoprotein (P-gp) and its potential mechanisms using in situ and in vitro models. The effective permeability of the typical P-gp substrate rhodamine 123 (R123) in colon was significantly increased from (1.69 ± 0.22) × 10 cm/s in the control group to (3.39 ± 0.417) × 10 cm/s (p < 0.01) in the 3.5 mM IP6 group. Additionally, IP6 can conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…5 P-gp is extensively expressed at the apical side of epithelial cells in the kidneys, liver, and especially intestine. P-gp acts as barrier and protects cells from exogenous xenobiotics by mediating efflux of compounds across the apical membrane of enterocytes, 7 thus attenuating absorption and facilitating excretion of its substrates.…”
Section: Introductionmentioning
confidence: 99%
“…5 P-gp is extensively expressed at the apical side of epithelial cells in the kidneys, liver, and especially intestine. P-gp acts as barrier and protects cells from exogenous xenobiotics by mediating efflux of compounds across the apical membrane of enterocytes, 7 thus attenuating absorption and facilitating excretion of its substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of phytic acid as a dietary component is not yet fully clarified, although its protective effects against cancer have been widely studied and proven, using cell lines, such as hepatocellular carcinoma (HepG2) and Caco-2 cells, and in vivo studies mainly performed with rats. [9,[83][84][85] In the first case, after a 48-hour-treatment, HepG2 viability was 23.8% in succinate dehydrogenase activity (3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT)) assay, and 32.4% in lactate dehydrogenase (LDH) assay, at 3.5 mM phytic acid. [85] For Caco-2 cells, the phytic acid decreased the effective permeability of the typical P-glycoprotein (P-gp) substrate rhodamine 123 (R123) by 50% in the colon, also at the 3.5 mM phytic acid.…”
Section: Cancermentioning
confidence: 99%
“…[85] For Caco-2 cells, the phytic acid decreased the effective permeability of the typical P-glycoprotein (P-gp) substrate rhodamine 123 (R123) by 50% in the colon, also at the 3.5 mM phytic acid. [84] Khatiwada et al ( 2006) [86] studied the effect of phytic acid and inositol on the induced colon tumor reduction in male rats. The results showed that 2 g 100 mL −1 phytic acid added to drinking water significantly reduced the occurrence of colon tumor in rats.…”
Section: Cancermentioning
confidence: 99%
“…Notably, SW480, HCT116 and Caco2 cells are commonly used cell culture models for the study of CRC in vitro (3,25). Caco2 cells express high levels of P-gp protein, and these cells are naturally multidrug-resistant (25,31,32). The IC 50 values of QTMP in SW480, HCT116 and Caco2 cells were 4.73 ± 1.12, 5.66 ± 1.32 and 6.14 ± 1.45 mg/ml, respectively, indicating only slight differences in the IC 50 values of QTMP in these CRC cell lines (Table 2).…”
Section: Qtmp Exhibits Potent Cytotoxic Activity Against Sensitive and Drug-resistant Crc Cells In Vitro And In Vivomentioning
confidence: 99%